Takwīnu al-Bīʾah al-ʿArabiyyah fī Maʿhad Khadījah bi al-Madrasah al-Thānawiyyah al-Islāmiyyah al-Ḥukūmiyyah al-Ūlā Jember li al-Sanah al-Dirāsiyyah 2022/2023 M: The Development of the Arabic Environment at Khadijah Institute in the First State Islamic Senior High School (MAN 1) Jember for the 2022/2023 Academic Year - Januari, Alya Eka; Hakim, Abdul (Critical Review of English-Arabic World Journal, 2023)
تُعَدّ البيئة أحد عوامل النجاح في تعليم اللغة العربية، إذ يصبح تعليم العربية أسهل عندما يتمّ بدعمٍ مستمر وتكرارٍ دائم. ويُعدّ معهد خديجة الداخلي أحد المؤسسات التعليمية التي تقدّم برامج لغوية، مثل تعميق اللغة العربية يوميًا، وذلك لأن فاعلية تعويد الطالبات على التحدّث باللغة العربية في حياتهن اليومية تُعدّ من العوامل المؤثّرة في تكوين البيئة اللغوية في معهد خديجة الداخلي. ويعود ذلك إلى أنّه في كل غرفة سكنية لا تكون جميع التخصصات الدراسية من العلوم الشرعية، في حين تكون طالبات هذا التخصص أكثر قدرة ونشاطًا في استخدام اللغة العربية. كما أن إجراء المحادثة اليومية باللغة العربية لا يمكن تحقيقه بشكل شامل لأن المعهد يضمّ تخصصات دراسية متعددة، وتكون الطالبات المتخصصات في العلوم الشرعية عادةً أكثر تمكّنًا من استخدام العربية. وتتركّز أسئلة البحث وأهدافه على الأنشطة والعوامل التي تساعد أو تعيق عملية تكوين البيئة العربية في معهد خديجة الداخلي بالمدرسة الثانوية الإسلامية الحكومية الأولى بجَمْبر للعام الدراسي 2022/2023م. وتعتمد هذه الدراسة على المنهج الوصفي النوعي، بينما يقوم تحليل البيانات على منهج مايلز وهَبَرْمان. وللتحقق من صحة البيانات استخدمت الباحثة أسلوب التثليث بالمصادر والمنهج. وقد توصّل البحث إلى وجود ثلاثة أنواع من الأنشطة اللغوية: الأنشطة اللغوية اليومية، والأنشطة اللغوية الأسبوعية، والأنشطة اللغوية الشهرية. أما العوامل المساندة في تكوين البيئة العربية فهي: 1) حماس الطالبات العالي للمشاركة في هذه الأنشطة، 2) امتلاك المعلّمات القدرة الجيدة على استخدام العربية ومرافقة الطالبات في ممارستها، 3) توفّر البنية التحتية المناسبة. بينما تتمثّل العوامل المعيقة في: 1) بعض الطالبات اللواتي يتصفن بالكسل أو عدم الانتباه أو الانشغال بالضحك مع الزميلات، فضلاً عن تركيز بعضهن على الدراسة المدرسية، 2) اختلاف تخصّصات الطالبات المقيمات في المعهد، مما يؤثر في توازن استخدام اللغة العربية بينهنّ. The environment is one of the success factors in teaching Arabic. Teaching Arabic will be easier if it occurs with reinforcement and there is continuous repetition. Khadija boarding school is one of the schools that offers language education such as the deep Arabic language every day, because the effectiveness of getting used to speaking in Arabic on a daily basis is one of the inhibiting factors in the formation of the language environment in Khadijah boarding school, because it is in every bedroom not all of the school's majors are religious sciences, while female students are active in speaking Arabic in this major. Daily conversation cannot be conducted in Arabic because in the institute itself it is divided into many school disciplines, of which religiously majored female students are usually better able to use Arabic. The questions and objectives of this study are focused on how the activities and factors that help and hinder the formation of the Arabic environment at the Khadijah boarding school in Islamic Senior High School One of Jember for the academic year 2022/2023 AD. The method of this research is the descriptive qualitative method and the method of analyzing this research is the method of Miles and Huberman. And for the validity of the data in this research using the triangular approach with sources and method. The results of this research are the three language activities, the daily language activities, the weekly language activities, and the monthly language activities. The factors contributing to the formation of the Arab environment are, 1) the students are very enthusiastic to participate in these activities, 2) the teacher who delivers the lesson has good Arabic and can accompany the students, 3) an appropriate infrastructure. And the hindering factors, 1) by some female students, some of whom are lazy, do not pay attention to their friends, and joke with their friends, and some of them focus on studying for school lessons, 2) the specializations of the female students who live